KECENDERUNGAN PELAKSANAAN PENELITIAN PENDIDIKAN MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU PADA TUGAS AKHIR (SKRIPSI) - Istighfari Istighfari; Merri Silvia Basri; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research contains trends or tendency in the implementation of research by students of the Japanese Language Study Program at the University of Riau, graduating in 2018-2022. The problems that will be discussed in this study, are the tendency of student thesis seen from the point of view of the chosen research methods and the length of time the thesis is being worked on. The purpose of this research is to describe the trend or any tendency of conducting educational research for students of the Japanese Language Education Study Program, University of Riau, that are graduating in 2018-2022. The method used in this study is a quantitative method with a descriptive approach. The sample used in this research is the graduate student thesis in 2018-2022, totaling 47 theses. The data analysis technique is described using descriptive statistical analysis using relative frequency distribution tables (percentage distribution) and using the mean formula to find the average length of time students are writing their thesis.Key Words: The Tendency, Research Methods, The Length of Time the Thesis is Being Worked on